A Tale of Confusion: How Tribunals Treat the Presence and Absence of Evidence of Actual Confusion in Trade Mark Matters - Scott, Paul (Victoria University of Wellington Law Review, 2001)
In determining whether two trade marks are likely to cause confusion or deception tribunals consider a number of factors. Two important ones are the presence or absence of evidence of actual confusion. With the presence of such evidence tribunals are more willing to find a likelihood of confusion. With the absence of such evidence tribunals are more willing to find no likelihood of confusion. However, contrary authority exists for both propositions. This article suggests a framework for examining both the presence and absence of actual confusion evidence. It argues that only after closely examining the circumstances of each case should a tribunal regard the presence or absence of actual confusion evidence as probative.